Understanding alliance ruptures : what do they look like? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Rosenblatt, Sara Elisabeth (Massey University, 2013)
The Therapeutic Alliance (TA) has a significant impact on treatment outcome. 'Ruptures' - rifts in the client-therapist relationship - threaten TA and carry a number of subsequent risks, including: further drops in TA, interrupted therapeutic progress and a greater likelihood of unilateral client termination. Successfully recognising a rupture may not only prevent these risks, but can provide a target for therapeutic work, and, when accompanied by successful repair, may produce TA levels that surpass prerupture levels. Despite knowledge that ruptures are common to treatment, research has not addressed whether therapists are skilled at recognising and understanding ruptures. This question is thwarted by the more foundational gap in knowledge: there is no description of what a therapist should be looking to recognise. The present research identifies a sampling of rupture indicators (72 items) using an emotion language context. These indicators are stimuli in a card-sorting task completed by two groups of participants: a New Zealand sample (N=33) and a native Japanese one (N=37). Similarity data derived from this task were analyzed using multidimensional scaling (MDS) to produce a unified three-dimensional model that sufficiently represents both samples. The identified dimensions on which rupture indicators are likely to vary are: Interaction Type (i.e. are the indicators a withdrawal or confrontational type), Derivation of Meaning (i.e. is the indicator biologically based or does it convey a socially constructed meaning?), and Subject Focus (is the indicator directed at the other, interpersonal, or at the self, intrapersonal). Also identified in the model were 12 different clusters, or kinds, of rupture indicators (e.g. physically aggressive, verbally defiant, submissive speech content, physiological distress). Conclusions are drawn from this analysis and recommendat5ions follow on ways to further validate this model. Also discussed are applications of this model to enhance training programs for rupture recognition, to improve recognition ability in practice and also to facilitate consistent rupture recognition strategies for research purposes. This may precipitate future research exploring correlations between rupture incidence rates, and presentation types according to therapist and client variables.
Keywords: Therapeutic alliance; Psychotherapy